(3QSGdI aj UfYI GdGSWQdGH GdeSJYeds - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3cd eG NWQ HGdHGd hJUhQ ai GdhbJ SCdfi CaQGO Yed (B( (3HMK(B) (3UfYI GdGSWQdGH GdeSJYed s
(3BNQgG (B:s
(3agPg gi CUfGa GdGSWQdGH Edi PcQfGgG ai Pdc GdcJGH hgh cJGH dCHi GdQjMGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3Ydjg Jedc deMeO Hf UfYGf Hf eMeO Hf YHO GddWjas
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B845s
Keywords: (3Gdadcs